PENDAPAT SISWA TENTANG PELAKSANAAN LAYANAN KONSELING KELOMPOK PENDAPAT SISWA TENTANG PELAKSANAAN LAYANAN KONSELING KELOMPOK PENDAPAT SISWA TENTANG PELAKSANAAN LAYANAN KONSELING KELOMPOK - Suryani suryani; Khairani Khairani (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
Service counseling the group constitute service that helps alleviating the problems who experienced by the learners  so  that  is  reached  developments  who  optimal.  Reality  on  the  ground  that  the  proces implementation counseling services the  group have not been effective in  helping  alleviating the  problems student.The aim of this research describe students' opinions about the implementation of counseling services group be seen from time the implementation, stage the implementation, the role of  group leader, the role members of the group and the achievement objectives counseling services the group. Types of descriptive research, with the findings the research, opinions students about the implementation of counseling service group in SMAN 6 Padang runs with well.